2000
DOI: 10.1021/ja993564f
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(IV)-Assisted [2 + 3] Cycloaddition of Nitrones to Coordinated Organonitriles. Synthesis of Δ4-1,2,4-Oxadiazolines

Abstract: [2 + 3] cycloaddition between acetonitrile ligands in the platinum(IV) complex [PtCl4(MeCN)2] and the nitrones -O+N(R3)C(R1)(R2) [R1 = H, R2 = Ph, o-C6H4OH, p-C6H4Me, p-C6H4OMe, p-C6H4NO2, p-C6H4NMe2, p-C6H4NMe2·HCl, R3 = Me; R1 = H, R2 = Ph, t Bu, R3 = CH2Ph] proceeds smoothly under mild conditions and gives the first examples of Δ4-1,2,4-oxadiazoline complexes, as a 1:1 mixture of two diastereoisomers, in 70−90% yields. The heterocyclic ligands were liberated almost quantitatively by rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 72 publications
8
79
0
Order By: Relevance
“…22,23 Two relatively stable aryl nitrile oxides, i.e., 2,4,6-Me 3 C 6 H 2 CNO and 2,4,6-(MeO) 3 C 6 H 2 CNO, 27 have been chosen as dipoles. The reaction between [PtCl 4 (EtCN) 2 ], exhibiting moderate solubility in CH 2 Cl 2 , and the nitrile oxides in a molar ratio of 1:4 proceeds smoothly in a suspension at room temperature and is complete after 1 day (Scheme 1), and the final products were isolated in good yields.…”
Section: Ndc(et)ondccmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Two relatively stable aryl nitrile oxides, i.e., 2,4,6-Me 3 C 6 H 2 CNO and 2,4,6-(MeO) 3 C 6 H 2 CNO, 27 have been chosen as dipoles. The reaction between [PtCl 4 (EtCN) 2 ], exhibiting moderate solubility in CH 2 Cl 2 , and the nitrile oxides in a molar ratio of 1:4 proceeds smoothly in a suspension at room temperature and is complete after 1 day (Scheme 1), and the final products were isolated in good yields.…”
Section: Ndc(et)ondccmentioning
confidence: 99%
“…20 A few years ago, within the framework of our continuous project on reactions of metal-activated nitriles (this topic has been reviewed by two of us 20 ), it was found that the platinum(IV) center in [PtCl 4 (RCN) 2 ] complexes provides sufficiently strong activation of the nitriles to assist the facile [2 + 3] cycloaddition between RCN ligands and various nitrones (R 1 )(R 2 )Cd(R 3 )-N + O -to achieve the first examples of ∆ 4 -1,2,4-oxadiazoline complexes [PtCl 4 (∆ 4 -1,2,4-oxadiazoline) 2 ]. 22,23 In this work, we endeavored to extend the [2 + 3] cycloaddition of complexed RCN species from nitrones to nitrile oxides. The main goals of this work are the following ones: (i) to determine whether the results disclosing the enhanced reactivity of Pt(IV)-bound nitriles are specific for dipoles of allyl anion type, 24 e.g., nitrones, or the reactions can be spread out to dipoles of the propargyl/allenyl anion type, 24 e.g., nitrile oxides; (ii) to develop a general route to 1,2,4-oxadiazoles which is based on the [2 + 3] cycloaddition between the metal-activated nitriles and nitrile oxides and to perform the synthesis under mild conditions, thus preventing the nitrile oxides from dimerizing.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4-oxdiazole complexes 136 and 138. [71,581] Also cyclic nitrones (e.g. pyrroline N-oxide) have been studied.…”
Section: Nitrile Complexesmentioning
confidence: 99%
“…The reactions of the complexes MCl 2 (NCR 1 ) 2 (M = Pd, Pt) and PtCl 4 (NCR 1 ) 2 with nitrones have extensively been studied among others by G. Wagner, [71,581,595] and have been looked at from every angle. [82,91b,594] This included questions of regiospecifity and stereospecificity, [585] the influence of the oxidation state of the metal ion, the nature of the nitrone [585] and the nitrile [586] (even including dialkylcyanamide), [586a] the biological (cytotoxic) activity, [595f] as well as methods for the cleavage of the heterocycle from the metal.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation